TINDAK PIDANA MENJUAL CHIP GAMES HIGGS DOMINO SECARA ONLINE KASUS PUTUSAN NO 124/PID.SUS/2023/PN. PGP: The Crime Of Selling Higgs Domino Games Chips Online Case Ruling No 124/PID.SUS/2023/PN. PGP - Setiawan Akbar Mahesa; Andi Widiatno (Reformasi Hukum Trisakti, 2025)
Massive online gambling in Indonesia, one of which is the Higgs Domino game, where in the game you need a chip coin to play this game, so there are people who deliberately sell the chip coins to other parties who want to play Higgs Domino gambling. The legal problem is what is the basis for the judge to impose criminal sanctions on the perpetrator of the crime of selling Higgs Domino game chips under Article 27 paragraph (2) of the ITE Law? and are the sanctions imposed on the perpetrators of the crime of selling Higgs Domino chips in accordance with the objectives of the punishment? This writing is included in normative research with its analytical descriptive nature and conclusions are drawn deductively. The results and conclusions of this paper show that the judge's basis for imposing criminal sanctions based on the provisions of Article 27 paragraph (2) of the ITE Law is incorrect and the sanctions imposed are not in accordance with the objectives of punishment, namely Reformation, Resraint, Retribution, and Deterrence